Understanding electro-mechanical engineering an introduction to mechatronics - Kamm, Lawrence J. (IEEE Press understanding science & technology series, 1996)
With a focus on electromechanical systems in a variety of fields, this accessible introductory text brings you coverage of the full range of electrical mechanical devices used today. You'll gain a comprehensive understanding of the design process and get valuable insights into good design practice. UNDERSTANDING ELECTROMECHANICAL ENGINEERING will be of interest to anyone in need of a non-technical, interdisciplinary introduction to the thriving field of mechatronics.